Simple and Selective Synthesis of Copper‐Containing Metal Nanoclusters Using (PPh3)2CuBH4 as Reducing Agent. Issue 3 (29th September 2020) - Shen, Hui; Han, Ying‐Zi; Wu, Qingyuan; Peng, Jian; Teo, Boon K.; Zheng, Nanfeng
Abstract: A simple and selective synthetic protocol, using (PPh3 )2 CuBH4 as reducing agent, for Cu‐containing mixed metal nanoclusters (NCs) is reported. Representative NCs include alkynyl‐protected [Ag25 Cu4 (PhCC)12 (PPh3 )12 Cl6 H8 ] 3+ (1 ), thiolate‐capped [AuCu14 (SR)12 (PPh3 )6 ] + (R = 4‐flurothiophenol) (2 ), and phosphine‐stabilized [Au9 Cu2 (PPh3 )8 Cl2 ] + (3 ), which are fully characterized by single‐crystal X‐ray diffraction analysis, electrospray ionization mass, nuclear magnetic resonance ( 1 H, 2 H, 13 C, and 31 P NMR), and optical measurements, respectively. This work demonstrates the advantages of using (PPh3 )2 CuBH4 as a reducing agent in the synthesis of Cu‐containing heterometallic NCs in terms of versatility as well as high yield and high purity of the products. This work may open the door to utilizing functional metal borohydride, as a new generation of reducing agent for the simple and selective synthesis of metal NCs. Abstract : NaBH4 shows little atomic accuracy in the synthesis of heterometallic metal nanoclusters. Demonstrated here is that (PPh3 )2 CuBH4 can be applied to efficient and selective synthesis of heterometallic nanoclusters. Three novel clusters are exampled, including alkynyl‐protected Ag25 Cu4, thiolate‐stabilized AuCu14, and phosphine‐capped Au9 Cu2, respectively. This synthetic method is simple, time‐saving, and temperature‐tolerate and products are in high‐yield and high‐purity.